2020
DOI: 10.3390/tropicalmed5040174
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Phlebotomine Sandflies in the Cave Area of Satun Province, Thailand

Abstract: Leishmaniasis, a sandfly-transmitted protozoan infection, is a neglected health threat in Thailand and the information on its vector is scarce. This study aimed to identify sandfly distribution, abundance, and environmental conditions of natural breeding sites in the cave areas of Satun Province, where previous cases of leishmaniasis were reported. Sandflies were collected during a six-month period using CDC light traps and modified emergence traps. Species distribution, relative abundance, and environmental c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…However, the occurrence of these species in a Previously listed as Phlebotomus in older publications humans and animals, as well as in the sand fly species identified, have all been previously reported in other studies in Thailand. The additional seven papers included one report on the detection of Bartonella in Vietnamese rodents [152], one on Vietnamese sand fly collections [153] and five on Thai sand fly collections [154][155][156][157][158]. In these seven papers, three new species of sand fly species were reported, including Sergentomyia rudnicki [154] (2 samples) and Phlebotomus papatasi [157] (16 samples) in Thailand, and Sergentomyia khawi [153] (27 samples) in Vietnam.…”
Section: Discussionmentioning
confidence: 99%
“…However, the occurrence of these species in a Previously listed as Phlebotomus in older publications humans and animals, as well as in the sand fly species identified, have all been previously reported in other studies in Thailand. The additional seven papers included one report on the detection of Bartonella in Vietnamese rodents [152], one on Vietnamese sand fly collections [153] and five on Thai sand fly collections [154][155][156][157][158]. In these seven papers, three new species of sand fly species were reported, including Sergentomyia rudnicki [154] (2 samples) and Phlebotomus papatasi [157] (16 samples) in Thailand, and Sergentomyia khawi [153] (27 samples) in Vietnam.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in Brazil indicated as caves were important for the protection, feeding, and breeding of sand flies 39,40 . Another study conducted in Thailand also supported that caves are potential breeding sites for sand flies 41 . In addition, rocky territories have been identified as the preferred ecology of the vectors 42 …”
Section: Discussionmentioning
confidence: 94%
“…39,40 Another study conducted in Thailand also supported that caves are potential breeding sites for sand flies. 41 In addition, rocky territories have been identified as the preferred ecology of the vectors. 42 In this study, the likelihood of developing CL was four times conducted in Kenya 27 and Colombia.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the morphological identification of female specimens, S. iyengari was the predominant species in several of the provinces investigated in this study, especially Chantaburi, Songkhla and Ubon Ratchathani provinces. The results of previous studies suggested that the species richness of sand flies in Thailand varied greatly among different provinces or habitats [ 19 , 32 – 36 ], possibly indicating that sand fly richness in Thailand might exhibit an area-specific distribution. These results indicated the need to investigate sand fly richness in several regions and habitats in order to obtain reliable information on sand fly species richness in Thailand.…”
Section: Discussionmentioning
confidence: 99%